Artificial intelligence and digitalization in China's education system: A systematic analysis of the policy framework and underlying strategies - Xing Liu-Schuppener (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2023)
The People's Republic of China is generally considered a pioneer in the development and application of artificial intelligence methods and digitalization solutions. This article is dedicated to a systematic review of the current AI and digitalization strategy in the education sector in China and places it in the wider context. It examines China-specific education policy strategies, how they are shaped, and which actors are crucial in this regard. The study is based on a systematic evaluation of publicly available sources using software-supported document analysis. For this purpose, 48 thematically relevant policy documents from the period of 2001 to 2022 were included. The results are categorized using an analysis framework and interpreted on the level of content as well as on the level of processes and relationships. The study thus provides an overview of the different phases and areas of education policy in China, central mechanisms of action, as well as political priorities and their changes over time.
urn:nbn:de:hbz:465-20230502-114406-4
Keywords: 330; China; policy; education; strategy; informatization; digitalization; AI; document analysis